Wodorowe testy oddechowe - metodyka, znaczenie w diagnostyce gastroenterologicznej - Trzepizur, Magdalena; Kudzin, Joanna; Toporowska-Kowalska, Ewa (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Breath tests are non-invasive diagnostic tools widely used in the diagnosis of ailments of the digestive system. The aim of this article is to discuss equipment maintenance, technical performance of hydrogen breath tests and the interpretation difficulties arising from the lack of clear standards for their execution.